Studi komparasi peraturan daerah cendana di provinsi NTT - S. Agung Sri Raharjo (Foresty Faculty of Hasanuddin University, 2013)
Regulation change as an effort to reduce the community trauma to the management of sandalwood in the past has not been influenced sandalwood stock in the field positively. Society is not aware of any changes in Sandalwood regulation. This study aims to determine the change in sandalwood regulation content. Research was conducted using descriptive approach, with content analysis techniques. The analysis showed that there are fundamental changes currently include aspects of general provisions, ownership, profit sharing and criminal provisions. Additional regulation for supporting this change is not available yet. This resulted the district regulation is less powerful applicable because some of the main activities in the management of a sandalwood mandated in the regulation, do not have a reference implementation. Therefore the local policy with more details implementation regulation is urgently needed.